Metabolic Clearance and Production Rates of Human Thyrotropin - Ridgway, E. Chester (1974)
Metabolic clearance (MCR) and production rates (PR) of human thyrotropin (hTSH) were determined by the constant infusion to equilibrium method 57 times in 55 patients. 16 control patients had a mean hTSH MCR of 50.7 ml/min. The mean hTSH MCR was significantly (P < 0.02) higher in 19 euthyroid men (51.6 ml/min) than in 12 euthyroid women (43.0 ml/min), but this apparent sex difference disappeared when the MCR were corrected for surface area, 25.8 (men) versus 25.2 ml/min per m(2) (women). Hypothyroid patients had significantly (P < 0.005) lower hTSH MCR (30.9 ml/min), and hyperthyroid patients had significantly (P < 0.05) higher hTSH MCR (60.9 ml/min) than controls. The hTSH MCR in patients with “decreased thyroid reserve” (40.9 ml/min), hyperfunctioning thyroid nodule (53.8 ml/min), and “empty sella syndrome” (46.6 ml/min) were not significantly different from controls. The mean hTSH PR in controls (104.3 mU/day) was significantly (P < 0.005) different from that in patients with “decreased thyroid reserve” (956 mU/day), hypothyroidism (4,440 mU/day), hyperthyroidism (< 43.9 mU/day) and a hyperfunctioning thyroid nodule (< 38.7 mU/day). In primary hypothyroidism intravenous triiodothyronine therapy (50 μg/day) for 10 days decreased the hTSH PR (from 4,244 to 2,461 mU/day) before changes in the hTSH MCR (from 33.1 to 33.7 mU/day) were observed. These studies have demonstrated that changes in the serum concentration of hTSH are mainly due to altered pituitary hTSH secretion with only a minor contribution from the change in hTSH MCR.